DIGITALIZATION OF SONGKET PROMOTION MEDIA IN NAGARI LUNTO, LEMBAH SEGAR DISTRICT, SAWAHLUNTO CITY - Marta, Revi; Anindya, Annisa; Havifi, Ilham (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
This community service activity involves partners, namely songket weavers in Nagari Lunto, Lembah Segar District, Sawahlunto City, West Sumatra Province. The partner's problem to date is the limited knowledge of partners about the use of new media as a promotional media that can be used to promote and sell songket. The purpose of this service is to design a solution that will help partner problems by conducting training, creating social media accounts for Nagari Lunto songket promotional media. The methods used are: providing solutions in order to overcome partner problems. Through needs analysis, work plans, activity implementation, and evaluation. The results of this service are as follows: 1). Increasing weavers' understanding of the importance of using the internet as a new media in promoting the songket they produce, 2) Implementing websites and social media in songket promotional activities in Nagari Lunto, 3). Increasing the quantity of songket sales by weavers in Nagari Lunto. The methods used in this service activity are 1). Empowerment through internet training for the community around the weaving village, 2) Training in creating social media accounts that are trending in current business promotional media, 3). Community empowerment through increasing weavers' participation in the importance of appropriate promotional media to promote silungkang songket weaving so that it can beat conventional media.